Upaya Mendorong Pola Hidup Sehat Masyarakat Kabupaten Takalar melalui Pelatihan Pembuatan Aneka Salad Sayur - Azis, Andi Asmawati; Kurnia, Nani; Putri Ulan Sari Patongai, Dian Dwi; Pratiwi, A. Citra (Jurnal Abdi Negeriku, 2022)
A healthy lifestyle in the community has become an important concern for policy makers, both at the national and international levels. This is because the application of a healthy lifestyle in the community is an important part in improving the quality and welfare of people's lives. One of the important aspects of a healthy lifestyle is diet. A good diet will support a healthy lifestyle. A good diet is not only related to the amount or portion of food consumed but also the quality of food which includes the nutritional content of each component. Vegetables are a component in foods that contain many nutrients that are useful for the body, but in fact the level of vegetable consumption in Indonesia is still relatively low. One of the contributing factors is the lack of variety in vegetable processing. Salad is a type of vegetable processed food that is very easy to make and has many benefits because it has a high nutritional content. Training activities as a solution to the problem of low levels of vegetable consumption in the community are carried out in collaboration with the MGMP Science Teacher group in Takalar Regency who are expected to be able to follow up to disseminate skills in processing various vegetable salads to meet community needs.